Analytical investigation on catenary action in axially-restrained reinforced concrete beams. (1st August 2019) - Wang, Shan; Kang, Shao-Bo
Highlights: An analytical model is proposed for predicting catenary action of beams. Parametric study is conducted on the effect of axial stiffness on catenary action. A simplified method is developed for the design of beams under catenary action. Abstract: Catenary action featuring axial tension forces plays a critical role in resisting the applied load when reinforced concrete beams with adequate axial restraints experience large deformations. It can be used as the last line of defence under some extreme scenarios. However, limited analytical studies are available at present to quantify the load capacity and the associated axial tension force. This paper describes an analytical study on catenary action in reinforced concrete beams. In the model, equilibrium and compatibility of beams are established, and the strains of steel reinforcement and the concrete are correlated to the global deformations of the beam. The fracture of bottom reinforcement at the mid-span is taken into account in formulating equilibrium and compatibility. The variation of vertical load and axial tension force with displacement can be obtained through the proposed model. The model is validated against experimental data and reasonably good agreement is obtained. The effects of axial stiffness on catenary action are investigated through the analytical model. Finally, a design method is proposed in accordance with analytical results to evaluate the catenary action capacity and the associated tension force.